PENGARUH MODERASI BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP HUBUNGAN PENERAPAN SISTEM AKUNTANSI PEMERINTAH, PARTISIPASI PENYUSUNAN ANGGARAN DAN KINERJA APARAT PEMERINTAH DAERAH (Studi Empiris Pada SKPD Pemerintah Provinsi Riau) - Raharjo, Niko Dwi; Taufik, Taufeni; Ratnawati, Vince (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study was aimed at finding out the effect of Implementation governmentaccounting system on performance of government apparatus. the effect ofparticipation in budget preparation on performance of government apparatus, theeffect of organizational culture to correlation Implementation government accountingsystem with performance of government apparatus, the effect of organizationalcommitment to correlation implementation government accounting system withperformance of government apparatus, the effect of organizational culture tocorrelation participation in budget preparation with performance of governmentapparatus, the effect of organizational commitment to correlation participation inbudget preparation with performance of government apparatus on ProvincialGovernment of Riau. This study belongs to quantitative research. The sample wasdetermined by purposive sampling technique. Collecting data using primary datacollection, this study uses questioner for 120 respondents. The data analysis wasdone by using multiple regression and Moderate Regression Analysis (MRA) withthe help of SPSS software. The result of this study showed: (1) Implementationgovernment accounting system had a positive and significant effect on performanceof government apparatus; (2) participation in budget preparation had a positive andsignificant effect on performance of government apparatus; (3) organizational culturevariable as mediating the effect of Implementation government accounting systemon performance of government apparatus, (4) organizational commitment variableas mediating the effect of implementation government accounting system onperformance of government apparatus; (5) organizational culture variable asmediating the effect of participation in budget preparation on performance ofgovernment apparatus, (6) organizational commitment variable as mediating theeffect participation in budget preparation on performance of government apparatuson Provincial Government of Riau.